Value-based fees : how to charge what you're worth and get what you charge - Weiss, Alan, 1946- (Wiley, 2021)
"In the 13 years since the second edition was published, we've seen the following developments which dramatically impact consultants starting in the profession or veterans in the profession. Remote means of delivering services, from workshops to facilitation, from strategy to M&A work. A waning of the power and repute of huge firms because of their cost and ponderous work methods, and a reception of less expensive, quicker small firms and solo practitioners. The mammals are scurrying amidst the dying dinosaurs. A globalization of economy (that will resume post-pandemic) making exported knowledge a key contributor to income (if it were considered formally as an export it would seriously shift the trade imbalance). The emergence of an African middle class, the decline of ancient dictators, and the growth of a huge potential marketplace in most countries on that continent. The growing abandonment of "career" and reliance on large companies and the inclination to forge one's own security and focus instead on a "calling." Advanced technology that effectually replaces meetings and keynote speeches delivered in person with Zoom and Livestream broadcasting of high quality. Tele-health demonstrating that "tele-consulting" is feasible and acceptable. Even therapy is being done this way today. A strong move from project work to advisory work which is as strong a shift as 30 years ago when I pioneered a shift from hourly billing to value-based fees. A huge change in social mores that include social consciousness, racial justice, and embrace of varying life styles. These are especially important in future strategy"--